Business BASIC - Bent, Robert J.; Sethares, George C. (California : Brooks/Cole Publishing Company, 1984)
This book is intended for an audience with no prior programming experience. A working knowledge of elementary algebra is the only mathematics needed to understand the material and complete the assignments successfully.
1. Data processing -- 2. Problem solving -- 3. A first look at basic -- 4. First session at the keyboard -- 5. Interacting with the computer -- 6. The computer as a decision maker -- 7. More on the print statement -- 8. Loops made easier -- 9. Data as part of a program -- 10. Top-down programming -- 11. String and numerical functions -- 12. Arrays -- 13. More on processing -- 14. Data files -- 15. Subroutines -- 16. Random numbers and their applications -- 17. Matrices.
Includes index.
Keywords: BASIC (COMPUTER PROGGRAM LANGUAGE)